State-space FDTD implementation of anisotropic perfectly matched layer - Ramadan, O (Iee-Inst Elec Eng, 2003)
New formulations based on the state-space approach are presented for implementing the anisotropic perfectly matched layer into the finite difference time domain (FDTD) algorithm. The formulations are where simple and independent from the material properties of the FDTD computational domain. Numerical tests are included to validate the proposed formulations.